Modelagem e controle de corpo completo usando álgebra de quatérnios duais aplicados e um manipulador móvel - Fredy Rolando Salazar Sangucho (2014)
The goal of this dissertation is to implement a technique of whole-body modeling and control for a mobile manipulator composed of a robotic manipulator with five degrees of freedom coupled to a non-holonomic mobile robot with differential traction and three degrees of freedom. The modeling is based on the dual quaternion algebra for finding the foward and differential kinematic models of the heterogeneous serial kinematic chain. A kinematic controller-in which the reference is given by the dual quaternion representing the end-effector pose-produces the robot movement and uses the whole-body Jacobian to generate, simultaneously, the control signal for all degrees of freedom of the redundant kinematic chain. Moreover, in order to improve the controller performance and extend its convergence region, we propose a cascade control in which the inner loop takes into consideration the non-holonomic constraints of the mobile robot by means of an inputoutout linearization controller. In order to evaluate the performance of the implemented algorithms, computer simulations and experiments on a real mobile manipulator were performed. The results obtained from the experimental point of view are shown to be acceptable, demonstrating the validity of the technique of whole-body modeling and control based on dual quaternion algebra.